Comprehensive Assessment of Reactogenicity and Safety of the Live-Attenuated Chikungunya Vaccine (IXCHIQ®) - Gabriele Maurer; Vera Buerger; Julian Larcher-Senn; Florian Erlsbacher; Stéphanie Meyer; Susanne Eder-Lingelbach; Juan Carlos Jaramillo (Vaccines, 2025)
Background/Objectives: This overview provides a comprehensive safety evaluation of the approved live-attenuated vaccine VLA1553 (IXCHIQ®) for active immunization for the prevention of disease caused by chikungunya virus (CHIKV) in clinical trials. Methods: Protocol-defined solicited systemic events (i.e., fever, arthralgia, myalgia, fatigue, and headache) and other unsolicited arthralgia-related events were evaluated. Additionally, during a regulatory review, a broader definition of adverse events of special interest (broad-definition AESIs) (fever and ≥1 AESI symptom within 30 days post-vaccination) was evaluated post hoc. Results: The most frequently reported solicited systemic events post-VLA1553 included fever (13.5%), arthralgia (17.2%), myalgia (23.9%), fatigue (28.5%), and headache (31.6%), with very few prolonged symptoms. The incidence of unsolicited arthralgia-related events (arthritis, osteoarthritis, musculoskeletal stiffness, joint stiffness, and joint swelling) was comparable between VLA1553 and placebo groups. Broad-definition AESIs were observed in 11.7% (361/3082) participants (VLA1553) and 0.6% (6/1033) participants (placebo), with a duration of 1–182 days (median: 4 days; prolonged broad-definition AESI [≥1 symptom lasting ≥ 30 days] occurred in 0.5% of participants) (VLA1553) and 4–27 days (median: 8 days) (placebo). Most symptoms contributing to broad-definition AESIs were solicited. In the VLA1553 group, the most common of these symptoms, in addition to fever, were headache (9.1% of participants), fatigue (8.6%), myalgia (7.0%), and arthralgia (5.2%). There were few severe cases (1.6% of participants in the VLA1553 group). Conclusions: In clinical trials, VLA1553 showed an acceptable safety profile that was consistent with other live-attenuated vaccines. The incidence of broad-definition AESIs was mainly limited to the immediate post-vaccination period, and broad-definition AESI symptoms were mostly solicited systemic adverse events.